2009
DOI: 10.1021/np9000976
|View full text |Cite
|
Sign up to set email alerts
|

Pronuciferine N-Oxide, a Proaporphine N-Oxide Alkaloid from Berberis coletioides

Abstract: Pronuciferine N-oxide (1), a proaporphine N-methyl-N-oxide alkaloid, along with the parent alkaloid pronuciferine (2) were isolated from Berberis coletioides. The structure of the new compound was determined by spectroscopic evidence. Compound 1 is the first naturally occurring proaporphinoid alkaloid with an N-oxide functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…Compound 1 was obtained as a white amorphous powder and its molecular formula was deduced to be C 21 [6] which was also isolated from S. epigaea in this study, strongly suggested a proaporphine alkaloid for 1. The main difference between them was that compound 1 possesses no N-methyl group which exists To clarify the absolute configuration of C-6a and C-2′ in 1, the ECD data of four possible structures were calculated and compared with experimental spectrum.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Compound 1 was obtained as a white amorphous powder and its molecular formula was deduced to be C 21 [6] which was also isolated from S. epigaea in this study, strongly suggested a proaporphine alkaloid for 1. The main difference between them was that compound 1 possesses no N-methyl group which exists To clarify the absolute configuration of C-6a and C-2′ in 1, the ECD data of four possible structures were calculated and compared with experimental spectrum.…”
Section: Resultssupporting
confidence: 57%
“…An unusual proaporphine alkaloid bearing an isopropanenitrile group at isoquinoline nitrogen, named epigasine A (1) and a new aporphine alkaloid, epigasine B (2), together with eight known proaporphine/aporphine alkaloids, pronuciferine (3) [6], dehydrodicentrine (4) [7], romerine (5) [8], romeline (6) [9], Nmethylcalycinine (7) [10], phanostenine (8) [11,12], dicentrine (9) [13], and N-methyllaurotetanine (10) [14] (Fig. 1) were isolated from the roots of S. epigaea.…”
Section: Introductionmentioning
confidence: 99%
“…B. tabiensis: Quevedo et al, 2008[ 101 ]. B. coletioides: Fajardo et al, 2009[ 34 ]. B. waziristanica: Hussain, 1992[ 52 ]).…”
Section: Chemical Diversity In Berberisunclassified
“…The additional ROESY correlation of H-6 0 a/H-12 0 indicated that H-6 0 a and H-12 0 were a syn-periplanar relationship and H-6 0 a was the b-orientation. 12 Furthermore, the electronic circular dichroism (ECD) spectra ( Fig. 3) of 1 showed negative trough (Dε, À1.61) and positive crest (Dε, þ4.75) at 273 and 232 nm, respectively, similar to those of sinomenine, suggesting that the absolute configuration of subunit 'a' was the same as that of sinomenine.…”
Section: Resultsmentioning
confidence: 95%